Exercise-Induced Modulation of Angiotensin II Responses in Femoral Veins From 2-Kidney-1-Clip Hypertensive Rats - Chies, Agnaldo Bruno; Spadella, Maria Angélica; de Oliveira, Priscila Ramos; Domeniconi, Raquel Fantin; de Mello Santos, Talita; Moreira, Roseli Peres; Rosales, Carla B.; Casarini, Dulce Elena; Navar, Luis Gabriel (Frontiers in Physiology, 2021)
The present study investigated the angiotensin II (Ang II) responses in rat femoral veins taken from 2-kidney-1clip (2K1C) hypertensive rats at 4 weeks after clipping, as well as the effects of exercise on these responses. In this manner, femoral veins taken from 2K1C rats kept at rest or exposed to acute exercise or to exercise training were challenged with Ang II or endothelin-1 (ET-1) in organ bath. Simultaneously, the presence of cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) were determined in these preparations by western blotting. In these experiments, femoral veins exhibited subdued Ang II responses. However, after nitric oxide (NO) synthesis blockade, the responses were higher in the femoral veins taken from animals kept at rest [0.137(0.049–0.245); n = 10] than those obtained in trained animals kept at rest [0.008(0.001–0.041); n = 10] or studied after a single bout of exercise [0.001(0.001–0.054); n = 11]. In preparations in which, in addition to NO synthesis, both the local production of prostanoids and the action of ET-1 on type A (ETA) or B (ETB) receptors were inhibited, the differences induced by exercise were no longer observed. In addition, neither ET-1 responses nor the presence of COX-1 and COX-2 in these preparations were modified by the employed exercise protocols. In conclusion, NO maintains Ang II responses reduced in femoral veins of 2K1C animals at rest. However, vasodilator prostanoids as well as other relaxing mechanisms, activated by ETB stimulation, are mobilized by exercise to cooperate with NO in order to maintain controlled Ang II responses in femoral veins.